(untitled) (Statistics, Optimization & Information Computing, 2025)
The main objective of this paper is to introduce a new class of sets namely micro generalized star semi closed set (briefly Mic-g∗s closed set) and micro genralized star semi open set (briefly Mic-g∗s open set) in micro topological spaces.